Knowledge and viewpoint of adolescent girls regarding child marriage, its causes and consequences - Somayyeh Naghizadeh; Mojgan Mirghafourvand; Azam Mohammadi; Marzieh Azizi; Saba Taghizadeh-Milani; Hadiseh Ganbari (BMC, 2021)
Abstract Background Child marriage is a violation of children's rights and it exposes them to social isolation and psychological damages. These negative effects are not limited to them and expands to the family and society as well. The present research aimed at determining the knowledge and viewpoint of adolescent girls regarding child marriage, its causes and consequences in the city of Tabriz-Iran, in 2020-2021. Methods This cross-sectional study was carried out on 300 adolescent girls who had records in the health centers in the city of Tabriz. The data were collected using the sociodemographic characteristics questionnaire, questionnaire of knowledge, and view of adolescent girls regarding child marriage, and its causes and consequences. The multivariate logistic regression model with adjusting the sociodemographic characteristics was used to determine the relationship between the viewpoint of adolescent girls about child marriage and their knowledge in this regard. Results The mean (SD) knowledge about child marriage was 6.70 (3.09) (score range: 0-11). The majority of the girls (85.4%) were against marriage before the age of 18 and only 16 girls (5.1%) of them agreed with marriage before the age of 18. Investigating the viewpoint of adolescent girls regarding the causes of child marriage revealed that the important issue leading to reduction of child marriage can be "intellectual, emotional, social, and economic maturity of girls plus their physical puberty (92.4% agree), increase in the girls' education (79% agree) and increasing girls' awareness regarding the consequences of early marriage in schools and media (69.6% agree). Illiteracy or lack of education of parents (64% agree), meeting the emotional needs (59.3% agree), family problems and conflicts (59.6% agree), and lack of exhilaration in daily life, especially in the rural regions and suburbs (58.3% agree) were among the reasons of increase of child marriage. The most important consequence of child marriage from the viewpoint of the girls is deprivation from the chance of education. The results of multivariate logistic regression model by adjusting the possible confounding variables, showed that girls who believed the appropriate age for marriage is under 20 were almost 13 times more likely to agree with child marriage than girls who believed the appropriate age for marriage is over 20 years (aOR = 13.82; 95% Cl 2.61-71.16 p = 0.002) and girls who opposed their parents' decision to marry under the age of 18 were less likely to agree with the child marriage than girls who did not oppose their decision (aOR = 0.09; 95% Cl 0.01-0.63 p = 0.016). Conclusions The results revealed a good level of knowledge and negative attitude to child marriage among the girls. The girls who disagreed with child marriage were more knowledgeable than the girls who agreed with child marriage. Thus, the increase of the level of knowledge of girls and their families regarding the consequences of early marriage and developing the culture for correcting the cultural beliefs and wrong social beliefs to prevent child marriage can decrease this damage to a great extent.